El nuevo teatro cordobés y el niño como espectador activo - Laura Fobbio (telondefondo. Revista de Teoría y Crítica Teatral, 2010)
In the sixties, the critics recognize the emergence of a "new cordovan theater." As part of this renovation, theatre "for children" carried out by cordovan artists raises aesthetic ruptures and ideological postulates in accordance with the political events that shake Argentina and the world at the end of the '60s and along the '70s. Beyond the specificity of each group, theatre performance "for children" share the experience of its makers in the National University of Cordoba, the horizontal and interdisciplinary approach as a work methodology, the respectful treatment of the active child-spectator, the free play as a way of communication, the theater as a possibility to change reality, the exile, among others.